PERSEPSI PENGGUNAAN E-PAYMENT DI ERA CASHLESS SOCIETY: PERAN NILAI ONLINE SHOPPING, MANFAAT E-PAYMENT DAN KEPATUHAN SYARIAH (SHARIA COMPLIANCE) - Dian Essa Nugrahini; Ahmad Hijri Alfian (Master of Management, Mataram University, 2023)
This study aims to examine three factors that influence differences in perceptions of using e-payments, namely the perceived value of online shopping, the benefits of e-payments and compliance with Islamic Sharia. This research adopts a quantitative methodology. Data collection was carried out using surveys and interviews. The population in this study are online shoppers, namely buyers who shop online. The results were concluded using the partial least squares structural equation modeling (PLS-SEM) technique. The variable that shows a significant effect on perceptions of using e-payments is the perceived benefits of using e-payments. There is a significant influence of the perceived e-shopping value on the perceived benefits of using e-payments. Meanwhile, the perceived e-shopping value does not have a significant effect on the perceived use of e-payments. In testing the moderating impact of compliance with Islamic Sharia does not show a significant effect. Keywords: Perceptions of Using E-Payment; Perceived Value; Benefits of E-Payment; Islamic Sharia Compliance; Cashless Society